Harnessing contactless monitoring technology for sows and piglets within farrowing pens: A critical review - Zheng He; Mahejabeen Hossain Nidhi; Zhaojin Guo; Li Lyu; Chuanyi Guo; Junhui Hou; Xiaoshuai Wang; Kai Liu (Smart Agricultural Technology)
Global pig production continues to expand in response to increasing demand for meat, placing greater emphasis on improving production efficiency, pig health, and welfare. Among all production phases, the periparturient and lactation periods are particularly critical for sow and piglet survival. To reduce high rates of pre-weaning mortality and ensure sow welfare, precise and continuous monitoring in farrowing pen environments for sows and piglets is essential. Compared to traditional manual observation, contactless monitoring technology offers promising and non-invasive solutions for real-time surveillance. Moreover, most existing reviews related to smart pig farming focused on a single task or technology across the whole pig production cycle. To the best of our knowledge, no existing review has investigated the application of contactless monitoring technology during specific phases of pig production, such as the lactation period. This review provides a comprehensive analysis of automated monitoring technology for sows and piglets during periparturient and lactation periods in farrowing pens. The literature retrieval strategy and publication trends in this area are first introduced. Subsequently, an overview of the commonly used contactless monitoring technology is described, including optical, infrared, audio, and radio-based sensing techniques. Their applications in farrowing pens are then presented, which span from daily monitoring of sows and piglets to event-specific tasks (e.g., farrowing prediction, lactation behavior analysis, crushing detection, and health indicator monitoring). Challenges related to data collection, annotation, model design, and deployment in commercial settings are also discussed. Finally, promising techniques and underexplored tasks for future research are highlighted. By identifying the achievements and persistent gaps in this area of research, this work aims to support the development of intelligent contactless monitoring systems within the farrowing pen environment, ultimately improving sow health and welfare, piglet preweaning mortality, and the sustainability of pig production.